Synthesis and characterization of Fe-doped CeO2 nanoparticles and their photocatalytic activities - Duangdao Channei (2018)
In this research, cerium oxide (CeO2) nanoparticles were synthesized by the homogeneous precipitation. Cerium nitrate hexahydrate and ammonia solution were used as precursors. A mixture of water and ethylene glycol was used as solvent. The ratio of ethylene glycol /water mixed solvent was 80% by volume of ethylene glycol. Pure CeO2 nanoparticles were yellow powder. Particle size was found to be in the range of 5-6 nm with BET specific surface area of 140.62 m2/g. TGA/DSC was used to find the appropriate temperature for calcination. X-ray diffraction analysis showed that the particles exhibited cubic fluorite structure. Then, cerium oxide nanoparticles were impregnated with ferric nitrate at 0.25, 0.50, 0.75, 1.00, 1.50 and 2.00 mol.% of CeO2 by calcining the mixture at 400 C°. Color of Fe-doped CeO2 became deeper yellow when mol.% Fe increased. Cerium oxide nanoparticles and the doped samples were characterized by using X-ray diffraction (XRD), the Brunauer, Emmett and Teller (BET), Transmission electron microscopy (TEM), Scanning electron microscopy (SEM) and Energy dispersive X-ray spectroscopy analysis (EDS). The photocatalytic activity of pure CeO 2 and Fe-doped CeO2 were investigated for the degradation of oxalic acid and formic acid under visible irradiation using photocatalytic reactor. The effect of Fe on photocatalytic activity of CeO2 nanoparticles was verified. It was found that Fe-doped CeO2 was more effective than pure CeO2. The photocatalytic activity of Fe-doped CeO2 for mineralization of formic acid was better than that of oxalic acid (the mineralization time to degrade formic acid was less than that of oxalic acid). The best result of photocatalytic activity for the degradation of oxalic was obtained from 2.00 mol.% Fe-doped CeO2 nanoparticles. 1.00 mol.% Fe-doped CeO2 demonstated the highest photocatalytic activity for the degradation of formic acid under visible irradiation. The enhanced performance observed for the Fe-doped CeO2 system was likely due to the formation of ferrioxalate and ferriformate complexes which could generate hydroxyl radical. ©2010 IEEE.